2016 Cambodia Enterprise Survey : Country Highlights - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Group conducted face-to-face interviews with top managers and business owners of 373 enterprises in Cambodia from February 2016 through June 2016. The Enterprise Survey (ES) sample is representative of Cambodia’s formal private sector. The ES covers several aspects of business environment along with measures of firm performance. The main highlights from the survey are: firms in Cambodia experienced sluggish annual sales growth but performed well in employment growth; investment financing from banks has deteriorated and is lower than in comparator economies; firms face high levels of corruption; electricity provision in Cambodia has become more reliable since 2013; and firms consider informal competitors as the biggest business environment obstacle.